Resilient Space Operations With Digital Twin for Solar PV and Storage - Shayan Ebrahimi; Mohammad Seyedi; S. M. Safayet Ullah; Farzad Ferdowsi (IEEE Open Access Journal of Power and Energy)
Space missions would not be possible without an available, reliable, autonomous, and resilient power system. Space-based power systems differ from Earth’s grid in generation sources, needs, structure, and controllability. This research introduces a groundbreaking approach employing digital twin (DT) technology to emulate and enhance the performance of a physical system representing a space-based system. The system encompasses three DC converters, a DC source, and a modular battery storage unit feeding a variable load. Rigorous testing across diverse operating points establishes the real-time high-fidelity DT, with root mean square error (RMSE) values consistently below 5%. The principal innovation leverages this DT to fortify system resilience against unforeseen events, surpassing the capabilities of existing controllers and autonomy levels. The approach offers an invaluable tool for scenarios where the system may not be primed for or physical access to components is limited. This research introduces a modular battery storage solution that seamlessly compensates for power shortages due to dust effects on the Lunar surface or unexpected system faults. This holistic approach validates the DT’s fidelity and underscores its potential to revolutionize system operation, safeguard against uncertainties, and expedite response strategies during unexpected contingencies. The proposed approach also paves the way for future development.